Hematite‐promoted nitrate‐reducing Fe(II) oxidation by Acidovorax sp. strain BoFeN1: Roles of mineral catalysis and cell encrustation. Issue 6 (13th July 2022) - Cheng, Kuan; Li, Han; Yuan, Xiu; Yin, Yunlu; Chen, Dandan; Wang, Ying; Li, Xiaomin; Chen, Guojun; Li, Fangbai; Peng, Chao; Wu, Yundang; Liu, Tongxu
Abstract: Although nitrate‐reducing Fe(II) oxidizing (NRFO) bacteria can grow sustainably in natural environments, numerous laboratory studies suggested that cell encrustation‐induced metabolism limitations and cell death occurred more seriously in the absence of natural minerals. Hence, a study on how natural minerals could affect NRFO is warranted. This study examined the impact of hematite on NRFO by Acidovorax sp. BoFeN1 with different electron donors (acetate and Fe(II), acetate alone, and Fe(II) alone) and with nitrate as an electron acceptor. When acetate and Fe(II) were used as the electron donors, the amount of Fe(II) oxidation and nitrate reduction was enhanced in the presence of hematite, whereas no promotion was observed when only acetate was added as an electron donor. Under the conditions with only Fe(II) added as an electron donor, the level of Fe(II) oxidation was increased from 3.07 ± 0.06 to 3.92 ± 0.02 mM in the presence of hematite and nitrate reduction was enhanced. This suggests that hematite promotes microbial nitrate reduction by accelerating the biological oxidation of Fe(II). The main secondary minerals were goethite and lepidocrocite. After adding hematite, the assemblage of iron minerals on the cell surface decreased, and the cell crusts became thinner, indicating that hematite effectively mitigated cell encrustation. Furthermore, hematite accelerated the chemical oxidation of Fe(II) by nitrite. Hence, hematite can promote the NRFO of Acidovorax sp. BoFeN1 via two possible pathways: (i) hematite acts as nucleation sites to mitigate cell encrustation; (ii) hematite catalyzes the biological and chemical oxidation of Fe(II) through the mineral catalysis effects. This study highlights the importance of existing iron minerals on NRFO and sheds light on the survival strategy of NRFO bacteria in anoxic subsurface environments.